Neurological Manifestations of COVID-19 - Andrianto Selohandono (Ahmad Dahlan Medical Journal, 2021)
COVID-19 disease has become a threat to global health. SARS-CoV-2 infection can cause damage to any other organs including the nervous system, which manifests as a neurological disorder. A number of neurological disorders have been reported in COVID-19 patients, including encephalopathy, stroke, myelitis, Guillain-Barre syndrome. The neurological manifestations in COVID-19 patients are varied and complex. A number of theories have been proposed to explain the pathomechanism behind the neurological diseases that develops in COVID-19 patients and are generally divided into direct and indirect effects of COVID-19. The direct routes involve invasion of the virus into the brain via olfactory, vascular pathways, or infiltration of infected immune cells; whereas indirect routes are the neurological consequences of systemic damage caused by viruses, such as inflammation, hypoxia, or hypercoagulable states. The neurological diseases experienced by COVID-19 patients can be caused by the pathophysiological process of the COVID-19 disease or other causes that coincide with viral infections.